Sensitive and specific LC-MS assay for quantification of digoxin in human plasma and urine - Kirby, Brian J.; Kalhorn, Tom; Hebert, Mary; Easterling, Tom; Unadkat, Jashvant D. (Biomedical chromatography, 2008)
Digoxin, a commonly prescribed cardiac glycoside with a narrow therapeutic window, is routinely used in pharmacokinetic studies to assess the in vivo activity of the drug efflux pump P‐glycoprotein. To minimize adverse events, a sub‐therapeutic dose of digoxin is usually administered, producing low plasma concentrations requiring a sensitive detection technique. Commonly available immunoassay techniques do not provide the required sensitivity to measure these low plasma concentrations and are potentially non‐specific in certain subject populations. Previously published mass spectrometric techniques require either large plasma volumes or a tandem mass spectrometer. To overcome these challenges we have developed a sensitive and specific LC‐MS method for the quantification of digoxin in small volumes of human plasma and urine. Plasma (1 mL) was extracted with methyl t‐butyl ether under basic conditions followed by LC‐MS detection of the sodium adducts of digoxin (803.4 m/z) and digitoxin (787.4 m/z, internal standard). Linearity and accuracy were demonstrated across a wide range of digoxin plasma concentration (0.05–1.5 ng/mL). This specific, sensitive, validated digoxin LC‐MS assay can be used to quantify sub‐therapeutic digoxin plasma concentrations in men and women (pregnant and non‐pregnant). Copyright © 2008 John Wiley & Sons, Ltd.